Pengaruh Promosi, Harga, Kualitas Produk terhadap Keputusan Pembelian Skincare Somethinc (Studi Kasus Pada Mahasiswa Manajemen FEB UNISMA Angkatan 2020) - Putri, Fadilah Adheyanti Arifin; Hidayati, Nur; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Beauty is something that is coveted by every woman from all walks of life. In general, beauty usually refers to a person's face and body shape. Someone can be said to be beautiful based on white, smooth, firm and clean facial skin. This research is located at the Islamic University of Malang, namely with 83 respondents, the method used in analyzing this data using multiple linear analysis methods using. The technique used in this research is purposive sampling. Purposive sampling is a sampling technique taken based on the criteria of the respondent, namely those who have purchased somethinc skincare. Based on the results of the study, it shows that promotion, price, product quality simultaneously influence the decision to purchase somethinc skincare. Partially promotion, price has an effect on purchasing decisions, and produlk quality has no effect on purchasing decisions for somethinc skincare. The research implications are expected for companies to consider more in prices, and improve product quality even better. Keywords: Promotions, Prices, Product Quality, And Purchase Decisions